Eu sou Moana: a linguagem construindo a protagonista de Moana: um mar de aventuras - Dalagñol, Nara (2024)
"I am Moana": language constructing the protagonist of Moana: a sea of ​​adventures is a work that aims to build, based on the concept of language proposed by Bakhtin, a methodological path to analyze the construction of the identity of Moana, the protagonist of the Disney animated film. To this end, we used Bakhtin's theoretical postulates from the 1950s, specifically, texts from the Addendum to the work Aesthetics of Verbal Creation, with the aim of: a) reflecting, based on the bibliographic review of Bakhtin's theoretical postulates from the 1950s, on the concept of language; b) identifying, based on the texts authored by Bakhtin published after 1950, concepts arising from the notion of language; c) defining notions underlying the concept of language; d) constructing a methodological path of enunciative study that allows us to analyze the construction of Moana's identity, verifying: 1) how dialogic relations occur in Moana's statements; 2) how Moana responsively understands other statements; 3) how Moana constitutes her identity based on relations of otherness; 4) how the intonation of the protagonist's statements manifests feelings and desires. Thus, the research is applied in nature, and is a bibliographical and documentary work, as well as exploratory. Thus, we defend the thesis that the notion of language and its interrelations make it possible to build a methodological path to analyze the construction of the identity of the protagonist of the film Moana: a sea of ​​adventures (2017). In this sense, we observe that Moana begins the journey as a teenager who seeks answers about herself, "to know who I am" (Moana, 2017), as well as needing to fulfill a task assigned by the sea. By stating "I am Moana [...] I will board my boat, cross the ocean, and restore the heart of Te Fiti" (Moana, 2017), she understands her individuality, knows her potential, her abilities, and defines her individuality. Thus, we see that Moana, in the dialogic and alterity relationship, especially with the statements of her father and grandmother, constitutes herself as an independent female subject, leader, capable of delimiting her destiny, distancing herself from the passive, submissive feminine archetype, dependent on others. Therefore, it is through language that the protagonist defines her identity, as well as constitutes herself as a subject.